Secondary Dengue Infection Elicits Earlier Elevations in IL-6 and IL-10 Levels - Espindola, Sonia Lorena (2024)
This study investigates the kinetics of interleukine-6 (IL-6) and interleukine-10 (IL-10) levels in dengue virus (DENV) infections during the febrile stage. Viremic patients were categorized into two phases based on anti-DENV IgM presence. Among 259 patients, 71% were in Phase I and 29% in Phase II. Secondary infections, accounting for 38.2% of cases, exhibited earlier elevations of IL-6 and IL-10 than primary infections, suggesting that pre-existing immune memory primes faster cytokine release. Thrombocytopenia and elevated aspartate transaminase (AST) levels were associated with Phase II, secondary infections, and hospitalization. Elevated IL-6 and IL-10 levels correlated with low platelet counts, linking them to clinical manifestations. The key finding is that IL-6 and IL-10 levels rise earlier in secondary infections compared to primary infections, whereas elevated cytokine levels typically occur later in the febrile phase. This study highlights the importance of cytokine dynamics in DENV infections, particularly during the early stages. The observation of cytokine concentration changes, especially in viremic samples, provides insights into the progression of dengue disease. Further research with broader cytokine panels is warranted to validate and expand these findings.